Tumor‐Induced Osteomalacia of the Head and Neck Region: A 10‐Year Tertiary‐Care Experience. (2nd September 2014) - Mathews, Suma S.; Rupa, Vedantam; Job, Anand; Mathew, John; Manipadam, Marie T.; Thomas, Nihal J.; Paul, Thomas V.
Abstract : Objectives: Oncogenic osteomalacia (OO) is a paraneoplastic syndrome seen in tumors of mesenchymal origin that secrete "phosphatonins, " like fibroblast growth factor‐23 (FGF‐23). They are characterized by hypophosphatemia and osteomalacia. These patients make remarkable recovery once tumors are localized and excised. The authors' aim was to study retrospectively the clinical, biochemical profile and follow‐up of subjects who presented with the features of OO of the head and neck region. Methods: Data of all the patients diagnosed to have OO from 2004‐2013 were collected using the computerized database. Results: Among the total 29 presentations of 27 with OO, 12 (44%) were found to have a histopathologically proven identifiable lesion. Nine (75%) of these were found to be in the head and neck region. The most common presenting symptoms in this subgroup were bone pains (78%) and proximal muscle weakness (56%). Rigid nasal endoscopy, blood pool scan, contrast‐enhanced computed tomography, and magnetic resonance imaging of head and neck region picked up 5 out of 6 (83%), 3 out of 7 (43%), 9 out of 9 (100%), and 3 out of 3 (100%) lesions, respectively. All patients underwent surgical excision, of which 56% are in partial and 44% in complete remission. Two patients had a recurrence at the same site after 5 years. Conclusions: The head and neck region was the most common site where tumor was localized in patients with OO. In all hypophosphatemic osteomalacia, where oncogenic osteomalacia is suspected, nasal endoscopy and imaging of the head and neck region should be done. Surgical excision remains the mainstay of treatment. These patients warrant long‐term follow‐up as a recurrence can occur several years after the initial response.